2000
DOI: 10.1128/mcb.20.21.8026-8034.2000
|View full text |Cite
|
Sign up to set email alerts
|

ets-2 Is a Target for an Akt (Protein Kinase B)/Jun N-Terminal Kinase Signaling Pathway in Macrophages of motheaten-viable Mutant Mice

Abstract: The transcription factor ets-2 was phosphorylated at residue threonine 72 in a colony-stimulating factor 1 (CSF-1)- and mitogen-activated protein kinase-independent manner in macrophages isolated from motheaten-viable (me-v) mice. The CSF-1 and ets-2 target genes coding for Bcl-x, urokinase plasminogen activator, and scavenger receptor were also expressed at high levels independent of CSF-1 addition to me-v cells. Akt (protein kinase B) was constitutively active in me-v macrophages, and an Akt immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 53 publications
5
59
1
1
Order By: Relevance
“…Maximum induction was observed 1 h after addition of PMA, which is 1 h before the peak level of PTHrP P3-specific transcript in response to PMA was reached ( Figure 1C). To activate the Ets2 protein, PMA could trigger phosphorylation at Thr 72 [33] by stimulating either the Raf/MEK-1/ERK1/2 or the phosphoinositide 3-kinase pathway [33,44]. As shown in Figures 1(D) and 2(B), we have already demonstrated that MEK-1 inhibitor PD98059 inhibits PMAinduced P3-dependent PTHrP expression and P3-dependent transcription.…”
Section: Pma Modulates Ets2 Activity In Mcf-7 Cellsmentioning
confidence: 64%
“…Maximum induction was observed 1 h after addition of PMA, which is 1 h before the peak level of PTHrP P3-specific transcript in response to PMA was reached ( Figure 1C). To activate the Ets2 protein, PMA could trigger phosphorylation at Thr 72 [33] by stimulating either the Raf/MEK-1/ERK1/2 or the phosphoinositide 3-kinase pathway [33,44]. As shown in Figures 1(D) and 2(B), we have already demonstrated that MEK-1 inhibitor PD98059 inhibits PMAinduced P3-dependent PTHrP expression and P3-dependent transcription.…”
Section: Pma Modulates Ets2 Activity In Mcf-7 Cellsmentioning
confidence: 64%
“…Despite the ability of U0126 to reduce phospho-ERK to control levels, and the clear efficacy of SB203580 in preventing the G2 arrest, p21 CIP1 expression was only partially inhibited by the combination of these drugs, suggesting that other pathways may also be important. Indeed, JNK can phosphorylate and activate Ets-2, c-Jun, JunB and ATF2, all of which have been proposed as regulators of the p21 CIP1 promoter (Kardassis et al, 1999;Smith et al, 2000). Unfortunately the lack of selective inhibitors of either JNK or p38g/d prevents us from further investigating the relationship between p21 CIP1 expression and SAPK activation at present.…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 phosphorylates Ets-1 at Thr38 and Ets-2 at Thr72, which increases their transactivational activity (26,27). A recent study of macrophages in motheaten-viable mice showed that Thr72 of Ets-2 is phosphorylated and activated by Akt-mediated Jun-N-terminal kinase (43). Akt also induces transcriptional activity of an Ets family member, PU.1, by phosphorylating a residue in its transactivation domain (44).…”
Section: Sustained Activation Of Erk1/2 Enhances Cell Survival By Accmentioning
confidence: 99%